ART2: a 3D parallel multiwavelength radiative transfer code for continuum and atomic and molecular lines. Issue 2 (19th March 2020) - Li, Yuexing; Gu, Ming F; Yajima, Hidenobu; Zhu, Qirong; Maji, Moupiya
ABSTRACT: ART 2 is a 3D multiwavelength Monte Carlo radiative transfer (RT) code that couples continuum and emission lines to track the propagation of photons and their interactions with the interstellar medium (ISM). The original ART 2 has been extensively applied to hydrodynamics simulations to study panchromatic properties of galaxies and ISM. Here, we describe new implementations of non-local thermodynamic equilibrium RT of molecular and atomic fine structure emission lines, and the parallelization of the code using a number of novel methods. The new ART 2 can efficiently and self-consistently produce a full spectrum that includes both continuum and lines such as [C ii ], [N ii ], [O iii ], Ly α, and CO. These essential features, together with the multiphase ISM model and the adaptive grid, make ART 2 a multipurpose code to study multiwavelength properties of a wide range of astrophysical systems from planetary discs to large-scale structures. To demonstrate the capability of the new ART 2, we applied it to two hydrodynamics simulations: the zoom-in Milky Way Simulation to obtain panchromatic properties of individual galaxies, and the large-scale IllustrisTNG100 Simulation to obtain global properties such as the line intensity mappings. These products are vital for a broad array of studies. By enabling direct comparison between numerical simulations and multiband observations, ART 2 provides a crucial theoretical framework for the understanding of existing and future surveys, and the synergy between multiband galaxy surveys and line intensity mappings. Therefore, ART 2 is a powerful and versatile tool to bridge the gap between theories and observations of cosmic structures.